Effect on the ensilage performance and microbial community of adding Neolamarckia cadamba leaves to corn stalks. Issue 5 (25th May 2020) - Wang, Yi; Zhou, Wei; Wang, Cheng; Yang, Fuyu; Chen, Xiaoyang; Zhang, Qing
Summary: To comprehensively evaluate the fermentation performance and microbial community of corn stalks (CS) silage mixed with Neolamarckia cadamba leaves (NCL), CS were ensiled with four levels (0%, 10%, 30% and 50% of fresh weight) of NCL for 1, 7, 14, 30, 60 days in two trials. The results showed that all silages were well preserved with low pH (3.60–3.88) and ammonia nitrogen content (0.08–0.19% DM). The silage samples with NCL displayed lower ( P < 0.05) acetic acid, propionic acid and ammonia nitrogen contents and lactic acid bacteria population during ensiling than control silages (100% CS). The addition of NCL also influenced the distribution of bacterial and fungal communities. Fungal diversity (Shannon's indices were 5.15–5.48 and 2.85–4.27 in trial 1 and trial 2 respectively) increased while the relative abundances of Lactobacillus, Leuconostocs, Acetobacter and two moulds ( Aspergillus and Fusarium ) decreased after added NCL. In summary, mixing NCL is a promising effective approach to preserve protein of CS silage and inhibit the growth of undesirable bacteria and mould, thus to improve the forage quality to some extent. Abstract : Most of corn stalk have been used as high‐fiber feed for ruminant animals in China. Neolemarckia cadamba leaves were rich in crude protein, crude fat, gross energy and organic matter, which can be used as a new type of forage for animals. Mixing the leaves of Neolamarckia cadamba is a promising effective approach to preserve protein of Corn stalk and inhibit the growth of undesirable bacteria and mold, thus to improve the forage quality to some extent.